Perbandingan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Number Head Together (NHT) Dengan Model Pembelajaran Teams Games Tournament (TGT) Pada Mata Pelajaran Ekonomi - Sulistiawati, Nurwinda; Hermawan, Yoni; Nurdianti, Raden Roro Suci (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The research conducted at SMAN 6 Tasikmalaya was motivated by the low learning outcomes of students in economic subjects by comparing the Number Head Together learning model with the Teams Games Tournament learning model in class XI IPS SMAN 6 Tasikmalaya in the 2023/2024 school year. The method used used quasi-experimental method with Nonequivalent Multiple Group Design. The population used in the study were all students of class XI IPS which amounted to 197 students. While the sample used for the first experimental class was class XI IPS 3 with a total of 39 students and used the Number Head Together learning model, while the sample used for the second experimental class was class XI IPS 4 with a total of 40 students and used the Teams Games Tornament learning model with sampling using Nonprobability Sammpling. Based on the results of the study explained that there was an increase in student learning outcomes using the Number Head Together learning model on international trade material, the average posttest value obtained by students was superior compared to the posttest value obtained through the Teams Games Tournament learning model, thus it can be concluded that in this study the Number Head Together learning model can improve student learning outcomes. Translated with DeepL.com (free version)